Features and Publication Rates of Scientific Abstracts Presented at a Rheumatology Congress EULAR 2008 - Yilmaz, Sedat; Kalyoncu, Umut; Cinar, Muhammet; Karadag, Omer; Koca, Suleyman Serdar; Simsek, Ismail; Dinc, Ayhan (J Michael Ryan Publishing Inc, 2013)
Objective: Various types of scientific abstracts are selected and presented at meetings and listed in abstract books. Recently, a systematic review has shown that 45% of 30,000 abstracts were published in a journal. The aim of this study was to determine the features of abstracts selected to be presented at a EULAR meeting (2008) and the corresponding publication rates. Methods: The EULAR 2008 Abstract Book was extracted, presented abstracts were assessed, their publication status was checked, and features related with publication rate were determined. The publication status of abstracts as of January 20, 2011, was verified using PubMed. Results: A total of 1,732 abstracts were assessed. Median publication duration was 13 (range: 0 to 31) months. Most of the abstracts (N = 339) were of multi-national origin. Sixty seven percent of abstracts were clinical and 563 (33%) abstracts were preclinical. We found that 601 of all abstracts (34.7%) had been published in a journal, and most of were published in a rheumatology journal. Fifty-seven percent of published abstracts were in journals with an impact factor higher than 4. The publication rate was correlated with presentation type, number of centers involved, trial design, and number of patients enrolled. Conclusions: We found that the publication rate of EULAR 2008 abstracts at 30 months was approximately 35%. This is a high rate compared to a previously published systematic review that investigated the publication rate of studies initially presented as abstracts in medical meetings, which reported the publication rate at 24 and 36 months as 20.7% and 28.1%, respectively. More than half of the published abstracts were accepted by high-impact journals. Presentation type, number of centers, trial design, and enrolled patient numbers were all correlated with the rate of publication.